Animated Video Learning Media in the Implementation of Cognitive Flexibility Learning to Improve Science Literacy and Design Thinking - Ni Komang Sari Mahayuni; I Wayan Widiana; I Nyoman Laba Jayanta (Thinking Skills and Creativity Journal, 2025)
The low ability of elementary school students' science literacy and design thinking is caused by the teacher's teaching method which is still conventional. Teachers do not utilize learning media in the learning process. This study aims to analyze the effectiveness of Animation Video learning media in the Implementation of Cognitive Flexibility Learning to improve Science Literacy and Design Thinking learning of fifth grade elementary school students. This development research uses the ADDIE model. The subjects of this study were 33 fifth grade elementary school students. The data collection methods and instruments used were questionnaires and essay tests. The data analysis techniques used were qualitative descriptive statistical analysis, quantitative descriptive statistical analysis, and inferential statistical analysis (t-test). The results of the study showed that the results of the correlated t-test showed a significance value (2-tailed) of 0.001 or p <0.05, which means that Animation Video in the Implementation of Cognitive Flexibility Learning on the material of animal locomotor organs is effective in improving the ability of Science Literacy and Design Thinking learning of fifth grade elementary school students. With this research, it is expected to provide a reference for readers or teachers at school.